Extending Analytical MHD Jet Formation Models with a Finite Disk Radius - Stute, Matthias; Tsinganos, Kanaris; Vlahakis, Nektarios; Matsakos, Titos; Gracia, José (Astrophysics and Space Science Proceedings, 2009)
The available analytical MHD models for jets, characterized by the symmetries of radial self-similarity (ADO, Analytical Disk Outflow solutions) in general have two geometrical shortcomings, a singularity at the jet axis and the non-existence of an intrinsic scale, i.e., the jets formally extend to radial infinity. The present study focuses on imposing an outer ejecting radius of the underlying accreting disk and thus providing a finite width disk-wind. The simulations are carried out using the PLUTO code. We study the time evolution of these modified analytical models and we investigate the rich parameter space and compare the results directly with observations.
Keywords: physics